2019
DOI: 10.5751/es-11016-240321
|View full text |Cite
|
Sign up to set email alerts
|

Natural resources knowledge socialization in Yucatan, Mexico: promoting a mutually beneficial society-nature relationship

Abstract: * Toledo VM. 2002. Ethnoecology: A conceptual framework for the study of indigenous knowledge of nature. Pages 511-522 in Stepp JR, Wyndham FS, Zarger RS, eds. Ethnobiology and Biocultural Diversity: Proceedings of the Seventh International Congress of Ethno biology. Athens (GA): international Society of Ethnobiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Similarly, learning using the loose part model. So in placing the learning model with local wisdom, [36] explaining the development of learning models is an ability that allows education and learning implementers to participate in the functioning of a wider social environment as well as the courage to utilize the environment and culture as well as cultural products. Even according to [37], between learning models, humans (students and teachers), with local cultural practices must be able to explore the complexity of local culture, as a whole that can maintain identity in the social and cultural processes of globalization.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, learning using the loose part model. So in placing the learning model with local wisdom, [36] explaining the development of learning models is an ability that allows education and learning implementers to participate in the functioning of a wider social environment as well as the courage to utilize the environment and culture as well as cultural products. Even according to [37], between learning models, humans (students and teachers), with local cultural practices must be able to explore the complexity of local culture, as a whole that can maintain identity in the social and cultural processes of globalization.…”
Section: Resultsmentioning
confidence: 99%
“…Documenting the defaunation of YP aquatic megafauna provides insight into the region's vulnerability to biodiversity loss. The rapid transformation of coastal ecosystems and the associated changes in sociocultural values can lead to the growing exploitation of natural resources (Castillo, Martínez & Viga, 2019; Rubio et al, 2019; Medina & Palafox, 2020; Rubio et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified different levels of government, NGOs, and communities that have carried out interdisciplinary work to create alternatives for the access, sustainable use, and management of some of the natural resources of the Yucatán coast [80,81]. However, further efforts and additional actions are needed to promote a harmonious relationship between the environment and society, as mentioned by Castillo-Burguete et al [82]. Kabisch et al [78] explored existing barriers and potential opportunities for increasing the effectiveness of implementing nature-based solutions and found that interand transdisciplinary studies are necessary to obtain a successful outcome.…”
Section: Outline Of Public Conservation Strategies For the Use And Management Of Beaches And Coastal Dunesmentioning
confidence: 99%